RESPONS GURU SEKOLAH DASAR TERHADAP PENGENALAN INTERNET OF THINGS UNTUK PEMBELAJARAN STEM - Jap Tji Beng; Mirabella Mirabella; Nina Perlita; Mei Ie; Alivia Fitriani Amanto; Desella Chandra; Sri Tiatri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Internet of Things (IoT)-based STEM learning is one of the technologies that will be used in the future. As the next generation, elementary level students need to understand the basics of using IoT. Elementary school teachers are also expected to have knowledge on IoT in order to educate their students. This study aims to describe elementary school teachers’ response to the introduction of the Internet of Things for science learning. The research was conducted using a qualitative participatory ethnography method. Researchers of this study consist of lecturers and students participating in Merdeka Belajar Kampus Merdeka (MBKM) research internship and the research participants were the Principal and 17 Elementary School Teachers in Kota S, Central Java. The research resulted in three findings: (a) Principals and Elementary School Teachers responded positively to the introduction of IoT, (b) Principals and teachers have not implemented the introduction of IoT in learning in elementary schools, (c) The introduction of IoT can be used as one of the compilers of Best Practice for the teachers. The results of the study can be used as an initial description for designing IoT-based STEM (Science, Technology, Engineering, and Mathematics) learning for elementary school students in the future.